Insights into the Immunopathophysiology of Severe COVID-19 in Metabolic Disorders - Shekhar, Skand; Copacino, Caroline E.; Barrera, Francisco J.; Hall, Janet E.; Hannah-Shmouni, Fady (Annals of the National Academy of Medical Sciences (India), 2020)
Coronavirus disease 2019 (COVID-19) has affected millions of people across the world but disproportionately and severely affects persons with metabolic disorders such as obesity, diabetes mellitus, and hypertension. In this brief review, we discuss the pathways of immune dysregulation that may lead to severe COVID-19 in persons with metabolic conditions.
Keywords: COVID-19; diabetes mellitus; hypertension; obesity